P340 Issues on implementing treat-to-target approach in Asia Pacific, Middle East and Africa: Reality, gaps, and way forward -APMA IBD Coalition. (30th January 2023) - Akyüz, F; An, Y K; Aniwan, S; Bui, H H; Chan, W P; Choi, C H; Chopdat, N; Connor, S; Desai, D; Flanagan, E; Kobayashi, T; Leong, R W; et al.
Abstract: Background: To understand the real-world issues and difficulties in implementing treat-to-target (T2T) approach in managing inflammatory bowel disease (IBD) patients in the Asia Pacific, Middle East and Africa (APMA) region. Methods: A structured survey of 10 questions was sent to 19 IBD specialists from 14 economies/countries in the APMA region between June and August 2022, followed by three hybrid roundtable discussions to identify, elaborate and validate the gaps and challenges in T2T adoption in their healthcare setting. The survey used a series of questions exploring experts' current practice and preference of treatment endpoints, diagnostic and monitoring tools, and major desirable improvement if resources are not constrained. Results: The two major gaps expressed by of IBD specialists in the APMA region are to early diagnose and treat IBD patients (61.1%), and the lack of trained IBD nurses (50%) (Figure 1.The major gaps in the diagnosis and monitoring of IBD in routine clinical practice in APMA). While T2T approach is widely accepted among IBD specialists across the APMA region, blood tests (such as CRP, ESR) and faecal calprotectin (FC) test are two commonly used modalities by 77.8% and 72, 2% IBD specialists, respectively However, the availability and cost of FC test is the second leading challenge (55.6%) faced by these specialists, with patient compliance being the most challenging (66.7%)(Figure 2.The biggest challenges in monitoring IBD patients in APMA). As to the most desired IBD monitoring tool, 88.9% considered the application of validated and reproducible intestinal ultrasound (Figure 3.Most desired IBD monitoring tool in APMA if resources are not a problem). The availability of trained IBD nurse (39%) and increasing awareness and training of general practitioner (33%) are the two most important factors that IBD specialists considered to improve care of IBD patients in the region (Figure 4.Major improvements required in diagnosis to improve IBD patient care in APMA). Conclusion: Considerable gaps in implementing T2T approach to managing IBD patients in the APMA region are identified via this survey by IBD specialists. Lack of training of general practitioners, IBD nurses and availability of affordable FC are common issues identified in this region, which would deserve implementation of new educational initiatives and resources reallocation.